Cognitive Change in Schizophrenia and Other Psychoses in the Decade Following the First Episode - Zanelli, Jolanta; Mollon, Josephine; Sandin, Sven; Morgan, Craig; Dazzan, Paola; Pilecka, Izabela; Reis Marques, Tiago; David, Anthony S; Morgan, Kevin; Fearon, Paul; Doody, Gillian A; Jones, Peter B; et al. (The American journal of psychiatry, 2019)
Objective:Schizophrenia is associated with a marked cognitive impairment that is widely believed to remain stable after illness onset. Yet, to date, 10-year prospective studies of cognitive functioning following the first episode with good methodology are rare. The authors examined whether schizophrenia patients experience cognitive decline after the first episode, whether this decline is generalized or confined to individual neuropsychological functions, and whether decline is specific to schizophrenia.Methods:Participants were from a population-based case-control study of patients with first-episode psychosis who were followed prospectively up to 10 years after first admission. A neuropsychological battery was administered at index presentation and at follow-up to patients with a diagnosis of schizophrenia (N=65) or other psychoses (N=41) as well as to healthy comparison subjects (N=103).Results:The schizophrenia group exhibited declines in IQ and in measures of verbal knowledge and of memory, but not processing speed or executive functions. Processing speed and executive function impairments were already present at the first episode and remained stable thereafter. The magnitude of declines ranged between 0.28 and 0.66 standard deviations. Decline in measures of memory was not specific to schizophrenia and was also apparent in the group of patients with other psychoses. Healthy individuals with low IQ showed no evidence of decline, suggesting that a decline is specific to psychosis.Conclusions:Patients with schizophrenia and other psychoses experience cognitive decline after illness onset, but the magnitude of decline varies across cognitive functions. Distinct mechanisms consequent to the illness and/or psychosocial factors may underlie impairments across different cognitive functions.